The forgotten pursuit: a carpentry centre in Karatara welfare settlement forged from the memories of woodcutters - Roos, Taline (University of the Free State, 2023)
This project embarks on an exploration and interpretation of the memories and narratives carved by the woodcutters and plantation laborers of Knysna. These memories serve as the foundation for the design of a carpentry centre, intended as a means for the upliftment of the welfare settlement, Karatara situated in the Western Cape. Many settlements near Knysna were established to address the forestry and welfare needs of the timber industry. The resulting question of this thesis: How can the creation of a Carpentry centre in Karatara be approached through the lens of recalling memories, archetypal references, and their integration within the existing community? This methodology seeks to delve deeper into the essence of place by investigating its historical underpinnings, with the aim of not only enriching the collective memory of Karatara but also anchoring this transformation through archetypal associations. This endeavour aspires to restore a sense of pride and ownership in a settlement that stands as a remnant of large industrial exploitation. In order to grasp the essence of Karatara, this research includes investigative approaches such as; personal stories, interviews, books and contemporary interpretations informed by the visual cues derived from collective memories of Karatara.
Dissertation(M.Arch.(Architecture))--University of the Free State, 2023
Keywords: Knysna, South Africa; Karatara welfare settlement; Woodcutters -- Personal narratives; Plantations, South Africa; Forestry, South Africa